ASSESSING HEPATIC TOXICITY IN Labeo rohita (Rohu Fish) INDUCED BY MICROPLASTIC POLLUTION IN FRESHWATER ECOSYSTEMS OF SARGODHA, PUNJAB (Journal of Medical & Health Sciences Review, 2025)
The problem of microplastics is now considered a sophisticated environmental concern exposing damages to aquatic and marine life systems across the globe. In Pakistan, the biological implications and existence of microplastics in aquaculture systems have not received considerable attention. The purpose of this study is to assess microplastic pollution within freshwater ponds of Sargodha, Punjab, and to investigate its physiological effects on Labeo rohita (Rohu), an economically important fish species in aquaculture. Existing research shows that polyethylene (PE), polypropylene (PP), and polystyrene (PS) microplastics are extensively documented in parts of the world. It is established that microplastics lead to increased oxidative stress, inflammation, and organ dysfunction in fish. Little information is available from Pakistan regarding bioaccumulation in locally consumed species, as well as the environmental impacts involved. Five pond locations (Chak No. 36, 39, 94, 98, and Asian Wala Gaoun) served as sample ponds for this study. These samples, along with the water samples, were analyzed for polymer specific functional groups using FTIR (Fourier-transform infrared spectroscopy). Assiduous contamination control measures strengthened reliability throughout the sampling and analysis phases. Based on the FTIR analysis results obtained, microplastic functional groups including O–H (3458 cm⁻¹), C=C (1639 cm⁻¹), C≡C/C≡N (2090 cm⁻) were detected in both the water samples and fish livers. High corrected area values were noted indicating significant bioaccumulation, particularly in the Labeo rohita livers which ostensibly undergo considerable oxidative stress and damage. These results were consistent across different sampling locations. The study shows that the freshwater ponds in Sargodha are heavily contaminated with microplastics, which have detrimental effects on the health of fish.